Α-Synuclein Seed Amplification Assays for Diagnosing Synucleinopathies: The Way Forward. (2nd August 2022) - Bellomo, Giovanni; De Luca, Chiara Maria Giulia; Paoletti, Federico Paolini; Gaetani, Lorenzo; Moda, Fabio; Parnetti, Lucilla
Abstract : Parkinson disease (PD) is the second most common neurodegenerative disease, and the most common synucleinopathy, as alpha-synuclein (α-syn), a prion-like protein, plays an important pathophysiologic role in its onset and progression. Although neuropathologic changes begin many years before the onset of motor manifestations, diagnosis still relies on the identification of the motor symptoms, which hinders to formulate an early diagnosis. Because α-syn misfolding and aggregation precede clinical manifestations, the possibility to identify these phenomena in patients with PD would allow us to recognize the disease at the earliest, premotor phases, as a consequence of the transition from a clinical to a molecular diagnosis. Seed amplification assays (SAAs) are a group of techniques that currently support the diagnosis of prion subacute encephalopathies, namely Creutzfeldt-Jakob disease. These techniques enable the detection of minimal amounts of prions in CSF and other matrices of affected patients. Recently, SAAs have been successfully applied to detect misfolded alpha-synuclein (α-syn) in CSF, olfactory mucosa, submandibular gland biopsies, skin, and saliva of patients with Parkinson disease (PD) and other synucleinopathies. In these categories, they can differentiate PD and dementia with Lewy bodies (DLBs) from control subjects, even in the prodromal stages of the disease. In differential diagnosis, SAAs satisfactorily differentiated PD, DLB, and multiple system atrophy (MSA) from nonsynucleinopathy parkinsonisms. The kinetic analysis of the SAA fluorescence profiles allowed the identification of synucleinopathy-dependent α-syn fibrils conformations, commonly referred to as strains, which have demonstrated diagnostic potential in differentiating among synucleinopathies, especially between Lewy body diseases (LBDs) (PD and DLB) and MSA. In front of these highly promising data, which make the α-syn seeding activity detected by SAAs as the most promising diagnostic biomarker for synucleinopathies, there are still preanalytical and analytical issues, mostly related to the assay standardization, which need to be solved. In this review, we discuss the key findings supporting the clinical application of α-syn SAAs to identify PD and other synucleinopathies, the unmet needs, and future perspectives.